Low-dose of phenolic rich extract from Annona squamosa Linn leaves ameliorates insulin sensitivity and reduces body weight gain in HF diet-induced obesity - Alkhalidy, Hana; Al-Nabulsi, Anas; Mhawish, Reham; Liu, Dongmin (Frontiers in Nutrition, 2023)
Obesity is associated with metabolic abnormalities that increase the risk and severity of several diseases. This study aimed to explore whether the aqueous extract of Annona squamosa Linn leaves (ASE) can ameliorate metabolic abnormalities associated with high fat (HF) diet-induced obesity. Forty-eight male Wistar rats were distributed among four treatment groups: a standard low-fat diet group, a high-fat (HF) diet group, and two HF diet groups with a daily oral dose of ASE (100 or 200 mg/kg body weights) administered for nine weeks. Daily energy intakes, body weight, blood glucose levels and glucose tolerance, and insulin tolerance were evaluated. At the end of the study, organs, and tissues were collected and weighed for analysis, and blood samples were collected to determine the serum insulin levels and serum liver enzymes. Total phenolic and flavonoid contents and 2,2-Diphenyl-1-picrylhydrazyl free radical antioxidant activity of the ASE were evaluated. Oral administration of the low dose of ASE to HF diet-fed rats significantly reduced the cumulative long-term food and caloric intake, and body weight gain without altering adiposity compared with untreated HF diet-fed rats. This outcome was accompanied by a significant improvement in insulin sensitivity and a reduction in fasting blood glucose (FBG) levels measured at weeks 6 and 9 of the study. The high dose of ASE had a shortterm effect on body weight gain and food and caloric intake, and in the long-term, it improved fasting blood glucoseFBG levels measured at weeks 6 and 9 of the study. The high dose of ASE resulted in hyperinsulinemia and high homeostatic model assessment for insulin resistance (HOMA-IR) value compared to healthy rats. Total phenolic and flavonoid contents were 74.9 ± 0.491 mg of gallic acid equivalent and 20.0 ± 0.091 mg quercetin equivalent per g of ASE, respectively. The antioxidant activity of ASE expressed as half-maximal inhibitory concentration (IC50) value was 8.43 ± 0.825 mg/mL. These data suggest that ASE can safely and potently reduce the development of insulin resistance-induced by HF diet feeding and lowering body weight gain in a dose-dependent manner.